A new N-C-31/9 polyene hydrocarbon from Antarctic bacteria - David Nichols; Peter Nichols; Thomas McMeekin (1995)
The non-saponifiable neutral lipid composition of nineteen bacterial strains isolated from Antarctic sea ice were analysed. Nine of these strains produced a novel highly unsaturated straight chain hydrocarbon as the major non-saponifiable neutral lipid component. The compound was identified as hentriacontanonene (n-C(31:9)) by mass spectrometry and the formation of n-C(31:10) following hydrogenation. The occurrence of n-C(31:9) also correlated with the production of polyunsaturated fatty acids (PUFA) by the bacterial strains. n-C(31:9) may therefore represent a novel biomarker for the location of PUFA-producing bacteria from environmental samples.